Spectral gain characteristics induced by 980 nm pumping band in a gain-Flattened EDFA - Sarmani, A.R.; Sheih, S.J.; Adikan, Faisal Rafiq Mahamd; Mahdi, M.A. (IOP Publishing, 2010)
We demonstrate the effect of inversion population ratio mediated by 980 nm pumping band on the gain spectra of a gain-flattened Erbium-doped fiber amplifier. The gain equalizing filter was designed at 977 nm and the amplifier was built in the four-stage arrangement. In the pumping structure, the 1480 nm lasers were maintained in the final gain block while the 980 nm band lasers were utilized in the first three blocks. These laser sources were arranged at several combinations of 977 and 980 nm wavelengths. Within these 3 nm spectrum, an absorption cross-section difference around 0.32 x 10(-25) m(2) contributed to a dispensable gain variation up to 3-dB. These inequalities were the results of variations in population inversion induced by the pump wavelength discrepancy. The findings show the importance of designing a filter at the specific absorption wavelength to allow the operation of consistent gain level.